2014
DOI: 10.1016/j.jsr.2013.12.005
|View full text |Cite
|
Sign up to set email alerts
|

The relative risk of involvement in fatal crashes as a function of race/ethnicity and blood alcohol concentration

Abstract: Introduction The literature presents a puzzling picture of Latinos being overrepresented in alcohol-related crashes, but not in noncrash drinking and driving. This report examines if, like other demographic variables in which some groups are at a higher crash risk than others (e.g., young drivers), different racial/ethnic groups face different crash risks Method This study compares blood-alcohol information from the 2006–2007 U.S. Fatality Analysis Reporting System (FARS) with control data from the 2007 U.S.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…Differential self-report in drowsy driving by race with systematic under-reporting by whites would lead to an artificial findings of elevated minority risk of drowsy driving. However, our finding of similar rates of self-reported drinking and driving by race when prior studies of objective crash data have demonstrated increased risk in blacks and Hispanics 46,47 suggests underreporting of drinking and driving is greater in minorities. If this pattern translates to drowsy driving, our findings may understate the magnitude of the actual disparity between white and minority drivers.…”
Section: Discussionsupporting
confidence: 56%
“…Differential self-report in drowsy driving by race with systematic under-reporting by whites would lead to an artificial findings of elevated minority risk of drowsy driving. However, our finding of similar rates of self-reported drinking and driving by race when prior studies of objective crash data have demonstrated increased risk in blacks and Hispanics 46,47 suggests underreporting of drinking and driving is greater in minorities. If this pattern translates to drowsy driving, our findings may understate the magnitude of the actual disparity between white and minority drivers.…”
Section: Discussionsupporting
confidence: 56%
“…Group differences were detected on ethnic composition (i.e., percent White vs. non-White including Black, First Nations, Asian, Hispanic or other), χ 2 (3) = 12.5, p = .006. Hence, to adjust for the potential influence of this factor on the findings (e.g., [ 80 ]), we entered ethnic composition as a covariate in analyses of substance use, parametric and simulated driving variables, and personality, cognitive, risk taking and neurobiological measures, both as a main and interaction (i.e., with group) effect.…”
Section: Resultsmentioning
confidence: 99%
“…Relatedly, we detected group differences in ethnic composition. As ethnic background can influence driving behaviour [ 80 ] and even traffic enforcement practices in some jurisdictions [ 96 ], we were obliged to use a post hoc statistical strategy to account for this potential confound. Finally, heterogeneity in the driving characteristics of our RD groups was found; in particular, some reckless driving and DWI events that were not documented in driving records (i.e., the basis of group member designation in this study) were self-reported.…”
Section: Discussionmentioning
confidence: 99%
“…It means that a driver coded as any race/ethnicity in FARS database died due to the traffic crash. Besides, the finding of an existing study [46] displayed that the White fatally injured drivers are overrepresented in single-vehicle, two-vehicle, and all vehicles crashes. Hence, significant differences of the probability of injury severity outcomes for White drivers were found in the current study.…”
Section: Discussionmentioning
confidence: 98%